E. coli Nissle 1917 ameliorates mitochondrial injury of granulosa cells in polycystic ovary syndrome through promoting gut immune factor IL-22 via gut microbiota and microbial metabolism - Luo, Man; Chen, Yuanyuan; Pan, Xiangyang; Chen, Hongmei; Fan, Lang; Wen, Yi (Frontiers in Immunology, 2023)
Objective: Gut microbiota and its metabolites have regulatory effects on PCOS related ovarian dysfunction and insulin resistance. Escherichia coli Nissle 1917 (EcN) is a genetically controlled probiotic with an excellent human safety record for improving gut microbiome metabolic disorders and immune system disorders. Here we focused to explore the application and effect of probiotic EcN on the gut microbiota-metabolism-IL-22-mitochondrial damage axis in PCOS. Methods: PCOS mice were constructed with dehydroepiandrosterone (DHEA) and treated with EcN, FMT or IL-22 inhibitors. Clinically control and PCOS subjects were included for further analysis. Serum and follicular fluid supernatant levels of sex hormones, insulin, glucose, cholesterol, and inflammatory factors were detected by ELISA and biochemical reagents. The pathological changes of ovarian tissues were observed by HE staining. The JC-1 level and COX4 gene expression in granulosa cells was detected by ELISA and RT-qPCR. The expressions of progesterone receptor A (PR-A), LC3II/I, Beclin1, p62 and CytC were detected by western blot. The number of autophagosomes in granulosa cells was observed by electron microscopy. 16S rRNA and LC-MS/MS were used to analyze the changes of gut microbiota and metabolism. Results: EcN promoted the recovery of sex hormone levels and ovarian tissue morphology, promoted the expression of IL-22, COX4 and PR-A in granulosa cells, and inhibited mitophagy in PCOS mice. EcN decreased the number of gut microbiota, and significantly increased the abundance of Adlercreutzia, Allobaculum, Escherichia-Shigella and Ileibacterium in PCOS mice. EcN improved metabolic disorders in PCOS mice by improving Amino sugar and nucleotide sugar metabolism pathways. IL-22 was positively associated with Ileibacterium, Adlercreutzia and Progesterone, negatively associated with RF39, Luteinizing hormone, Testosterone, N−Acetylglucosamin, L−Fucose and N−Acetylmannosamin. FMT reconfirmed that EcN ameliorated mitochondrial damage in granulosa cells of PCOS mice by gut microbiota, but this process was blocked by IL-22 inhibitor. Clinical trials have further demonstrated reduced IL-22 levels and mitochondrial damage in granulosa cells in PCOS patients. Conclusion: EcN improved IL-22 level and mitochondrial damage of granulosa cells in PCOS mice by promoting the recovery of sex hormone levels and ovarian tissue morphology, inhibiting the amount of gut microbiota, and promoting amino sugar and nucleotide sugar metabolism.